Molecular radionuclide imaging of pancreatic neoplasms. (July 2019) - Panda, Ananya; Garg, Ishan; Johnson, Geoffrey B; Truty, Mark J; Halfdanarson, Thorvardur R; Goenka, Ajit H
Summary: Pancreatic neoplasms have high morbidity and dismal prognosis. Substantial progress in translational research and advances in scanner technology have resulted in rapid integration of molecular radionuclide imaging of pancreatic neoplasms into mainstream clinical practice. Metabolic imaging with 18 F-FDG PET has extensive utility in the staging, assessment of treatment response, and follow-up of pancreatic ductal adenocarcinoma. Integrated PET/MRI has the potential to further expand this utility and lead to innovative applications. Somatostatin receptor PET imaging has had a profound effect on the evaluation and management of pancreatic neuroendocrine tumours. Peptide receptor radionuclide therapy is a new frontier in personalised medicine because it customises treatment to the unique biological features of a patient and the molecular signature of the patient's tumour. Further investigation is needed to optimise use of advanced molecular imaging techniques and novel radiotracers to achieve better outcomes for patients with pancreatic neoplasms.